A Christmas wish for Corduroy - Freeman, Don; Wheeler, Jody; Freeman, Don 1908-1978. (New York, New York Viking, Penguin Young Readers, an imprint of Penguin Random House LLC, 2017)
A teddy bear in the toy department of a big store receives a new name and a new home from Santa.
Originally published in slightly different format in 2014.
Accelerated Reader AR
111827
Keywords: Santa Claus -- Fiction; Board books; Teddy bears -- Fiction; Christmas -- Fiction; Juvenile Fiction -- Classics; Juvenile Fiction -- Holidays & Celebrations -- Christmas & Advent; Juvenile FictionJUVENILE FICTION -- Toys, Dolls & Puppets; Corduroy (Fictitious character); Board books; Christmas fiction; Fiction; Juvenile works; Children's stories -- Pictorial works